Recognizing and Evaluating Science Teaching in Higher Education: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Student ratings have long been used by many institutions of higher education as a primary form of summative evaluation of teaching. In recent years, studies have brought into question the validity of student ratings, highlighting the need for more effective evaluation methods that recognize and reward evidence-based teaching practices. To begin to frame the national conversation around the reform of teaching evaluation, the Roundtable on Systemic Change in Undergraduate STEM Education convened a 2-day workshop September 11-12, 2019, to discuss issues around recognizing and evaluating science teaching in higher education. Participants included experts in the fields of teaching and learning, as well as faculty from a range of institutional types, engaged in evaluation reform. This publication highlights the presentations of the workshop
Keywords: Education

Building Capacity for Teaching Engineering in K-12 Education - National Academy of Engineering; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Engineering education is emerging as an important component of US K-12 education. Across the country, students in classrooms and after- and out-of-school programs are participating in hands-on, problem-focused learning activities using the engineering design process. These experiences can be engaging; support learning in other areas, such as science and mathematics; and provide a window into the important role of engineering in society. As the landscape of K-12 engineering education continues to grow and evolve, educators, administrators, and policy makers should consider the capacity of the US education system to meet current and anticipated needs for K-12 teachers of engineering. Building Capacity for Teaching Engineering in K-12 Education reviews existing curricula and programs as well as related research to understand current and anticipated future needs for engineering-literate K-12 educators in the United States and determine how these needs might be addressed. Key topics in this report include the preparation of K-12 engineering educators, professional pathways for K-12 engineering educators, and the role of higher education in preparing engineering educators. This report proposes steps that stakeholders - including professional development providers, postsecondary preservice education programs, postsecondary engineering and engineering technology programs, formal and informal educator credentialing organizations, and the education and learning sciences research communities - might take to increase the number, skill level, and confidence of K-12 teachers of engineering in the United States.
Keywords: Education

Roundtable on Data Science Postsecondary Education: A Compilation of Meeting Highlights - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Established in December 2016, the National Academies of Sciences, Engineering, and Medicine's Roundtable on Data Science Postsecondary Education was charged with identifying the challenges of and highlighting best practices in postsecondary data science education. Convening quarterly for 3 years, representatives from academia, industry, and government gathered with other experts from across the nation to discuss various topics under this charge. The meetings centered on four central themes: foundations of data science; data science across the postsecondary curriculum; data science across society; and ethics and data science. This publication highlights the presentations and discussions of each meeting.
Keywords: Education; Computers and Information Technology; Math, Chemistry, and Physics

Biological Collections: Ensuring Critical Research and Education for the 21st Century - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Biological collections are a critical part of the nation's science and innovation infrastructure and a fundamental resource for understanding the natural world. Biological collections underpin basic science discoveries as well as deepen our understanding of many challenges such as global change, biodiversity loss, sustainable food production, ecosystem conservation, and improving human health and security. They are important resources for education, both in formal training for the science and technology workforce, and in informal learning through schools, citizen science programs, and adult learning. However, the sustainability of biological collections is under threat. Without enhanced strategic leadership and investments in their infrastructure and growth many biological collections could be lost. Biological Collections: Ensuring Critical Research and Education for the 21st Century recommends approaches for biological collections to develop long-term financial sustainability, advance digitization, recruit and support a diverse workforce, and upgrade and maintain a robust physical infrastructure in order to continue serving science and society. The aim of the report is to stimulate a national discussion regarding the goals and strategies needed to ensure that U.S. biological collections not only thrive but continue to grow throughout the 21st century and beyond.
Keywords: Biology and Life Sciences

Branches from the Same Tree: A National Convening on the Integration of the Arts, Humanities, and STEMM in Higher Education: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
In its 2018 report The Integration of the Humanities and Arts with Sciences, Engineering, and Medicine in Higher Education: Branches from the Same Tree, a committee of the National Academies of Sciences, Engineering, and Medicine pointed to an emerging body of evidence suggesting that integration of the arts, humanities, and STEMM fields - science, technology, engineering, mathematics, and medicine - is associated with positive learning outcomes that may help students enter the workforce, live enriched lives, and become active and informed members of a modern democracy. On April 12, 2019, the National Academies held a national convening in Washington, DC, to review, extend, and disseminate the committee's findings. At the convening, which was part of a series of events held across the United States, committee members, students, faculty members, and others discussed the future of higher education, the benefits of integration, and examples of integration that have proven to have positive effects. In addition, the convening featured dramatic readings that illustrated some of the issues involved with integrating the arts, humanities, and STEMM fields. This publication highlights the presentations of the event.
Keywords: Education

Changing Expectations for the K-12 Teacher Workforce: Policies, Preservice Education, Professional Development, and the Workplace - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Teachers play a critical role in the success of their students, both academically and in regard to long term outcomes such as higher education participation and economic attainment. Expectations for teachers are increasing due to changing learning standards and a rapidly diversifying student population. At the same time, there are perceptions that the teaching workforce may be shifting toward a younger and less experienced demographic. These actual and perceived changes raise important questions about the ways teacher education may need to evolve in order to ensure that educators are able to meet the needs of students and provide them with classroom experiences that will put them on the path to future success. Changing Expectations for the K-12 Teacher Workforce: Policies, Preservice Education, Professional Development, and the Workplace explores the impact of the changing landscape of K-12 education and the potential for expansion of effective models, programs, and practices for teacher education. This report explores factors that contribute to understanding the current teacher workforce, changing expectations for teaching and learning, trends and developments in the teacher labor market, preservice teacher education, and opportunities for learning in the workplace and in-service professional development.
Keywords: Education

Action Collaborative on Preventing Sexual Harassment in Higher Education: Year One Annual Report of Member Activities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The Action Collaborative's Year 1 Annual Report summarizes the Action Collaborative's collective progress in the 2019-2020 year, identifies areas for future focus, discusses trends in members' reported areas of work, and highlights work shared by some member organizations.
Keywords: Education

Strengthening Sustainability Programs and Curricula at the Undergraduate and Graduate Levels - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Over the past decade there has been a growing interest in sustainability education in colleges and universities across the United States, with a marked increase in the number of undergraduate and graduate degree programs, research institutes, and centers focused on sustainability. Evidence-based core competencies for interdisciplinary sustainability programs can provide suitable guidance for curricular and program development, research, policy, communication, and pedagogical approaches at academic institutions. They can also serve as a guide for students to select academic programs and potential career options, a reference for employers to understand qualifications of graduates, and the foundation for a potential specialized accreditation for interdisciplinary sustainability programs. The growing demand for well-qualified sustainability professionals within the public, private, and nonprofit sectors also points to the value of developing core competencies. Strengthening Sustainability Programs and Curricula at the Undergraduate and Graduate Levels provides expert insights for strengthening the emerging discipline of sustainability in higher education in the United States. This report describes the local, national, and global landscape related to sustainability education; examines the history and current status of sustainability education programs in the United States and globally; discusses employment prospects for sustainability graduates in terms of the opportunities and the skills that employers seek; and addresses diversity, equity, and inclusion in sustainability-related education and employment.
Keywords: Education

Re-envisioning Promotion and Advancement for STEM Faculty: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Faculty in science, technology, engineering, and medicine (STEM) are expected to excel in their technical work, teaching, and professional service. Their career advancement is often determined by academic peers evaluating accomplishments in these three areas. Recently, however, there is a growing concern that the evaluation of those accomplishments and traditional incentive systems are misaligned with some of the values and missions of higher education institutions, such as student learning, public engagement, and innovative research. Debates about current advancement systems also point to a body of research on the negative effects of traditional advancement criteria on the academic environment and workforce, including the influence of systemic and individual biases on the promotion and advancement of women and individuals from underrepresented populations. To examine and potentially re-envision advancement pathways for all STEM faculty, the National Academies of Sciences, Engineering, and Medicine convened academic leaders, scientists, engineers, medical professionals, scholars, philanthropists, and representatives from higher education associations and research funding agencies in October 2019. The Convocation on Re-envisioning Promotion and Advancement for STEM Faculty: Aligning Incentives with Values addressed challenges with the current system of faculty advancement and considered changes to promotion practices. Particular emphasis was placed on aligning faculty reward pathways to institutional and departmental missions and values. This publication highlights the presentation and discussion of the convocation.
Keywords: Education

NASA's Science Activation Program: Achievements and Opportunities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Aeronautics and Space Administration (NASA) is one of the United States' leading federal science, technology, engineering, and mathematics (STEM) agencies and plays an important role in the landscape of STEM education. In 2015, NASA's Science Mission Directorate (SMD) created the Science Activation (SciAct) program to increase the overall coherence of SMD's education efforts, to support more effective, sustainable, and efficient use of SMD science discoveries for education, and to enable NASA scientists and engineers to engage more effectively and efficiently in the STEM learning environment with learners of all ages. SciAct is now transitioning into its second round of funding, and it is beneficial to review the program's portfolio and identify opportunities for improvement. NASA's Science Activation Program: Achievements and Opportunities assesses SciAct's efforts towards meeting its goals. The key objectives of SciAct are to enable STEM education, improve U.S. scientific literacy, advance national education goals, and leverage efforts through partnerships. This report describes and assesses the history, current status, and vision of the program and its projects. It also provides recommendations to enhance NASA's efforts through the SciAct program.
Keywords: Education

Teaching K-12 Science and Engineering During a Crisis - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The COVID-19 pandemic is resulting in widespread and ongoing changes to how the K-12 education system functions, including disruptions to science teaching and learning environments. Students and teachers are all figuring out how to do schooling differently, and districts and states are working overtime to reimagine systems and processes. This is difficult and stressful work in the middle of the already stressful and sometimes traumatic backdrop of the global pandemic. In addition, students with disabilities, students of color, immigrants, English learners, and students from under-resourced communities have been disproportionately affected, both by the pandemic itself and by the resulting instructional shifts. Teaching K-12 Science and Engineering During a Crisis aims to describe what high quality science and engineering education can look like in a time of great uncertainty and to support practitioners as they work toward their goals. This book includes guidance for science and engineering practitioners - with an emphasis on the needs of district science supervisors, curriculum leads, and instructional coaches. Teaching K-12 Science and Engineering During a Crisis will help K-12 science and engineering teachers adapt learning experiences as needed to support students and their families dealing with ongoing changes to instructional and home environments and at the same time provide high quality in those experiences.
Keywords: Education

Reopening K-12 Schools During the COVID-19 Pandemic: Prioritizing Health, Equity, and Communities - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The COVID-19 pandemic has presented unprecedented challenges to the nation's K-12 education system. The rush to slow the spread of the virus led to closures of schools across the country, with little time to ensure continuity of instruction or to create a framework for deciding when and how to reopen schools. States, districts, and schools are now grappling with the complex and high-stakes questions of whether to reopen school buildings and how to operate them safely if they do reopen. These decisions need to be informed by the most up-to-date evidence about the SARS-CoV-2 virus that causes COVID-19; about the impacts of school closures on students and families; and about the complexities of operating school buildings as the pandemic persists. Reopening K-12 Schools During the COVID-19 Pandemic: Prioritizing Health, Equity, and Communities provides guidance on the reopening and operation of elementary and secondary schools for the 2020-2021 school year. The recommendations of this report are designed to help districts and schools successfully navigate the complex decisions around reopening school buildings, keeping them open, and operating them safely.
Keywords: Education; Health and Medicine

Building Educational Equity Indicator Systems: A Guidebook for States and School Districts - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
How can states and schools use data to support their efforts to improve educational equity? Building Educational Equity Indicator Systems: A Guidebook for States and School Districts, provides information to help state and school district leaders develop ways of tracking educational equity within their preK – 12 systems. The guidebook expands on the indicators of educational equity identified in the 2019 National Academies report, Monitoring Educational Equity, showing education leaders how they can measure educational equity within their states and school districts. Some of the indicators focus on student outcomes, such as kindergarten readiness or educational attainment, while others focus on student access to opportunities and resources, such as effective instruction and rigorous curriculum. Together, the indicators provide a robust picture of the outcomes and opportunities that are central to educational equity from preK through grade 12. For each indicator of educational equity identified in the report, the guidebook describes what leaders should measure and what data to use, provides examples of data collection instruments, and offers considerations and challenges to keep in mind. The guidebook is meant to help education leaders catalogue data they already collect and identify new data sources to help them fill gaps.
Keywords: Education; Behavioral and Social Sciences

Quality of Life, Preventing Elder Abuse, and Fostering Living Well After a Dementia Diagnosis: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On July 8, 2020, the Committee on Developing a Behavioral and Social Science Research Agenda on Alzheimer's Disease and Alzheimer's Disease-Related Dementias hosted a public workshop via webcast. This Proceedings of a Workshop-in Brief summarizes the key points made by the workshop participants during the presentations and discussions.
Keywords: Behavioral and Social Sciences; Health and Medicine

Understanding Nursing Home, Hospice, and Palliative Care for Individuals with Later-Stage Dementia: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On July 7, 2020, the Committee on Developing a Behavioral and Social Science Research Agenda on Alzheimer's Disease and Alzheimer's Disease-Related Dementias hosted a public workshop via webcast. This Proceedings of a Workshop-in Brief summarizes the key points made by the workshop participants during the presentations and discussions.
Keywords: Behavioral and Social Sciences; Health and Medicine

Reopening U.S. Research Universities: Confronting Long-Standing Challenges and Imagining Novel Solutions: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On July 21, 2020, the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Engineering, Medicine and Public Policy hosted a virtual workshop, Reopening U.S. Research Universities: Confronting Long-Standing Challenges and Imagining Novel Solutions. Attracting more than 500 participants, the workshop provided an overview of the current situation facing U.S. research universities and explored key questions that the research enterprise must address to build a more effective and resilient 21st century research university. This publication highlights the presentation and discussion of the workshop.
Keywords: Education

School Success: An Opportunity for Population Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Education and health care significantly influence well-being and health outcomes, especially throughout adolescence. In fact, doctors note that performance in school is highly reflective of a child's current and future health. Despite knowledge of this connection, pediatricians are rarely aware of their patients' school performance and have a limited understanding of the education system. Fostering collaboration and aligning efforts within the health and education sectors is a critical step towards building stronger and healthier communities. On June 14, 2018, the National Academies convened a workshop to discuss how efforts within the health sector can support children's education from pre-kindergarten through 12th grade and to explore the barriers between these sectors. The committee also examined case examples of health-education collaboration and opportunities in policy. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Educating Health Professionals to Address the Social Determinants of Mental Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The social determinants of mental health involve the economic, social, and political conditions into which one is born that influence a person's mental health - and, in particular, that affect the likelihood a person raised in deficient or dangerous conditions often associated with poverty will develop persistent mental health challenges throughout his or her life. To explore how health professions education and practice organizations and programs are currently addressing social determinants that contribute to mental health disparities across the lifespan, the Global Forum on Innovation in Health Professional Education of the National Academies of Sciences, Engineering, and Medicine hosted a workshop in Washington, DC on November 14-15, 2019. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Alzheimer's Disease and Related Dementias: Experience and Caregiving, Epidemiology, and Models of Care: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On August 14, 2019, the Committee on Developing a Behavioral and Social Science Research Agenda on Alzheimer's Disease and Alzheimer's Disease-Related Dementias convened a public workshop in Washington, D.C., as part of the study "Developing a Behavioral and Social Science Research Agenda on Alzheimer's Disease and Alzheimer's Disease-Related Dementias." As the first public event of the study, the workshop was designed to inform the public about the study and to gather information on how dementia affects individuals, families, and communities; the epidemiology of dementia; and how best to provide care to individuals with dementia. To achieve these goals, the workshop included four panel discussions: sponsors' perspectives on the study; perspectives from individuals living with Alzheimer's disease and other dementias and caregivers; epidemiological perspectives; and a discussion on models of care initiatives. This Proceedings of a Workshop - in Brief summarizes the key points made by the participants.
Keywords: Behavioral and Social Sciences; Health and Medicine

Challenging Questions about Epidemiology, Care, and Caregiving for People with Alzheimer's Disease and Related Dementias and Their Families: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
On October 17, 2019, the Committee on Developing a Behavioral and Social Science Research Agenda on Alzheimer's Disease and Alzheimer's Disease-Related Dementias hosted a public workshop in Washington, D.C., as part of the study "Developing a Behavioral and Social Science Research Agenda on Alzheimer's Disease and Alzheimer's Disease-Related Dementias." The workshop included six presentations by six authors of papers commissioned by the committee; these presentations were followed by a panel on measuring the effects of caregiving, including discussants who serve on the advisory panel to the committee. This Proceedings of a Workshop - in Brief summarizes the key points made by the workshop participants during the presentations and discussions.
Keywords: Behavioral and Social Sciences; Health and Medicine